Pathways towards resilient urban food systems - Claereboudt, Etienne; Alonso, Silvia; Awinoh, Martha; Halliday, Jess; Lenci, Lucia; Heck, Simon; Coyne, D.L.; Nyambura, Ivy; Roothaert, Ralph L.; Kibira, Mary; Kumar, S.; Salam, Md. Abdus; et al. (RUAF, 2024)
Food systems are facing unprecedented challenges from multiple shocks and stresses, including climate events, pandemics, geopolitical events, and economic crises. People, assets and infrastructures throughout supply chains are vulnerable to the impacts, and the consequences for food and nutrition security, livelihoods and economic development, and social equity can be dramatic.